From Regulation to Ethics: The Legal Effectiveness of Smart Village Policy through Village SDGs and Maqāṣid al-Sharīah - Sheila Kusuma Wardani Amnesti; Hasnan Bachtiar; Rayno Dwi Adityo; Siti Zulaichah (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2025)
Digital transformation in rural areas through the Smart Village concept has become a key strategy in sustainable development. Ministerial Decree No. 55 of 2024 on General Guidelines for Smart Village Development serves as the legal foundation for implementing the Smart Village policy, which aligns with the achievement of the Sustainable Development Goals (SDGs). By limiting the regulatory analysis to Ministerial Decree No. 55 of 2024, this article examines: (1) data standards and connectivity, (2) data protection and privacy, (3) financing and procurement, and (4) multi-stakeholder collaboration. The assessment of policy success is framed through five maqashid al-shariah dimensions: hifz al-din (ethical and inclusive governance), hifz al-nafs (health, safety, and food security), hifz al-aql (education and digital literacy), hifz al-nasl (family welfare and environmental sustainability), and hifz al-mal (economic empowerment and asset governance). Specifically, we contextualized our findings through case studies of Ponggok and Grajagan. The findings indicate that although the legal framework is clear, it remains limited to symbolic information and technology (ICT) infrastructure projects. Law enforcement and legal culture, which require partnerships among village officials, facilitators, and residents, receive insufficient attention. Other barriers include human resources, weak digital infrastructure, and poor coordination across actors. We recommend issuing a Village Regulation (Perdes) to operationalize Ministerial Decree No. 55 of 2024, which establishes data standards that are connected and easy to use, includes data protection clauses, and appoints trained village digital stewards. This study is intentionally limited to Ministerial Decree No. 55 of 2024; other regulations are noted as limitations and avenues for future research.